2023
DOI: 10.3390/plants12132415
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes of Leaf Spectral Properties and Rapid Chlorophyll—A Fluorescence under Natural Cold Stress in Rice Seedlings

Abstract: Nowadays, hyperspectral remote sensing data are widely used in nutrient management, crop yield forecasting and stress monitoring. These data can be acquired with satellites, drones and handheld spectrometers. In this research, handheld spectrometer data were validated by chlorophyll-a fluorescence measurements under natural cold stress. The performance of 16 rice cultivars with different origins and tolerances was monitored in the seedling stage. The studies were carried out under field conditions across two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…When the concentration of heavy metals in the soil increases, the content of heavy metals in different parts of rice usually increases as well, resulting in a stress effect [ 43 ]. As the stress of heavy metals in rice increases, some of the cellular structures are damaged, resulting in a decrease in chlorophyll content, which is reflected in differences in leaf spectra [ 44 , 45 ]. Therefore, we successfully inverted the content of heavy metals (Cd and As) in soil by spectral transformation, characteristic analysis, and modeling of rice leaf spectra.…”
Section: Discussionmentioning
confidence: 99%
“…When the concentration of heavy metals in the soil increases, the content of heavy metals in different parts of rice usually increases as well, resulting in a stress effect [ 43 ]. As the stress of heavy metals in rice increases, some of the cellular structures are damaged, resulting in a decrease in chlorophyll content, which is reflected in differences in leaf spectra [ 44 , 45 ]. Therefore, we successfully inverted the content of heavy metals (Cd and As) in soil by spectral transformation, characteristic analysis, and modeling of rice leaf spectra.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated the impact of cold stress on chlorophyll a fluorescence and leaf reflectance across various crop species [37][38][39][40][41][42][43][44]. For instance, research on winter oilseed rape cultivars under cold stress has shown declines in the maximal fluorescence and electron transport rate, coupled with changes in quantum yield and non-photochemical quenching [37].…”
Section: Introductionmentioning
confidence: 99%
“…Soybean exhibited a decreased maximum quantum efficiency of PSII in the dark-adapted state and impaired photosynthesis due to cold stress [41,42]. Variations in absorbance, reflectance, and transmittance under cold stress in rice have been used to distinguish between tolerant and sensitive genotypes, with the range of 525-535 nm proving the most stable and wavelengths above 700 nm being the most sensitive in the reflectance curve [43]. In maize, cold stress mainly affected reflectance between 500 and 600 nm, as well as around 700 nm, with spectral indices indicating decreased chlorophyll levels and an increased carotenoid/chlorophyll ratio in cold-exposed plants [44].…”
Section: Introductionmentioning
confidence: 99%
“…This dataset was captured by the CI-710 s SpectraVue Leaf Spectrometer (Cid-Bioscience, Camas, WA, U.S.A.). The absorbance, reflectance, and transmittance of albino plants were measured under natural cold stress in a temperate rice-growing area [1] . The experiment was carried out in field conditions at the seedling stage.…”
mentioning
confidence: 99%